WMicaD: A New Digital Watermarking Technique Using Independent Component Analysis. (20th January 2008) - Nguyen Nguyen, Thang Viet Thang Viet; Patra Patra, Jagdish Chandra Jagdish Chandra; Meher Meher, Pramod Kumar Pramod Kumar
Abstract : This paper proposes a new two-mark watermarking scheme that is based on the independent component analysis (ICA) technique. The first watermark is used for ownership verification while the second one is used as the copy ID of the image. Using a small-sized support image, the extraction is carried out on size-reduced level, bringing computational advantage to our method. The new method, undergoing a variety of experiments, has shown its robustness against attacks and its capability of detecting tampered area in the image.